Validación de la escala de carga de trabajo en trabajadores peruanos - Calderón de la Cruz, Gustavo Alexis (2018)
ABSTRACT The objective of this study was to validate of the Workload Scale in Peruvians. The sampling was intentional and included -170 industrial workers of a chemical and detergent company (83 women) -predominantly with technical education, all workers of a company located in Metropolitan Lima. A) confirmatory factor analysis was applied to evaluate the dimensionality of the items and the equivalence between men and women, b) reliability estimates for internal consistency, and c) a linear regression of demographic variables on the workload were estimated. A one-dimensional factorial structure was found, and the metric equivalence of the items was similar between men and women; the reliability was acceptable and, the intensity of the workload varied slightly according to the type of labor contract of the worker.